Innovation of Digital Population Identity Application at the Population and Civil Registration Service of Semarang City - Aryo Prasojo, Ridwan; Yuniningsih, Tri; Hidayati, Rizki (Universitas Medan Area, 2025)
The Digital Population Identity Application is an application that aims to help the public carry out population document services. However, the application in Semarang City is still not optimal. Poor response from the public regarding the application and user targets that have not been achieved. This study aims to analyze innovation and driving and inhibiting factors of the Digital Population Identity application at the Semarang City Population and Civil Registry Office. The type of qualitative descriptive research. This study uses Rogers' innovation attribute theory and Rogers' driving and inhibiting factors. The results of the innovation of the Digital Population Identity Application in Semarang City have been maximized even though some things are not optimal. In terms of complexity, it has not been maximized because the public experiences technical obstacles experienced by the community; the ease of use of the application is less than optimal because the public feels that the socialization carried out by the government is not massive enough. The driving factor is the effort to change from the agent, and the inhibiting factors are the characteristics of innovation, Communication channels, and social systems. The suggestions that can be given are that Dispendukcapil provides evaluation aspirations for residents if they experience difficulties, utilizes existing human resources effectively by inviting sub-districts, urban villages, and RT/RWs, and increases content regarding IKD, conducting routine evaluations on community aspirations forums, and taking firm action against perpetrators of hoax spreaders.